(untitled) (Research, Society and Development, 2021)
Objective: to report the importance of the Nursing consultation for guidance in preparation for colonoscopy. Method: a descriptive study, of the experience report type, about the performance and experiences of nurses working in the endoscopy unit, in a large hospital located in the South of Brazil, carried out in May 2021. Results: colonoscopy allows complete visualization of the mucosa of the colon and terminal ileum and is considered a complete method in the investigation of colorectal diseases. The adequate intestinal preparation is a determining factor for the ability to perform the exam and the duration of the procedure. The nurse plays a fundamental role in the assistance provided to the individual in the days preceding the exam related to the guidelines and conducts for its success. These should be individual and specific for each patient, considering the age group, comorbidity, level of education, and the degree of difficulty to perform the preparation. Final considerations: based on the practice carried out by the nurses, it was observed that the lack of guidance or the patients’ failure to adequately prepare for the exam can cause some complications during the exam or even make it unfeasible, and to minimize possible setbacks that may occur, the performance of a trained and qualified nurse ensures patient safety and provides comprehensive care, in a planned and appropriate way, for the exam.